World War II the definitive visual guide : from Blitzkerieg to Hiroshima (Dorling Kindersley Limited, 2015)
A visual history of the people, politics and events of the epic conflict that shaped the modern world, World War II. It helps you find out about key battles, political and economic forces, individual leaders and technological advances that influenced the course of the war.